Development of Articulate Storyline Media to Improve Students' Critical Thinking Skills - Safna Maulidiya; Sri Sami Asih (STAI Hubbulwathan Duri, 2025)
The integration of technology into elementary mathematics education remains limited, leading to challenges in fostering students' critical thinking skills, especially in abstract topics such as flat shapes. This study aims to develop and evaluate the effectiveness of Articulate Storyline-based learning media in improving the critical thinking skills of fifth-grade students on the topic of rectangular flat shapes (squares and rectangles). The research employed a Research and Development (RD) approach based on the Borg and Gall model. The participants were 34 fifth-grade students from SD Negeri Tambakaji 03, Semarang. Data were collected through expert validation questionnaires (material and media experts), student response questionnaires, and pretest-posttest instruments. Validity and reliability tests were conducted to ensure the quality of the instruments, and effectiveness was analyzed using the N-gain and t-test. The results show that the developed Articulate Storyline media achieved a validity score of 92%, indicating it is highly feasible for classroom use. Student responses also showed positive acceptance and high practicality. Statistical analysis revealed a significant improvement in students’ critical thinking skills, with an average N-gain score of 0.7084, classified as high. In conclusion, the use of Articulate Storyline media effectively enhances students' critical thinking abilities in mathematics, particularly in learning about flat shapes. The study supports the incorporation of interactive digital media as a pedagogical tool to bridge the gap between abstract mathematical concepts and engaging learning experiences at the elementary level.